Antidromic atrioventricular reentrant tachycardia in a patient with Wolff‐Parkinson‐White syndrome and unapparent preexcitation: A case report. Issue 6 (10th September 2021) - Enzan, Ayano; Takenaka, Sou; Ueno, Akihiko; Sakakibara, Masayoshi; Koyama, Terumasa; Uemura, Shiro
Abstract: This is a case of antidromic AVRT in a patient with unapparent preexcitation, and we could successfully diagnose and treat with the careful interpretation of wide QRS tachycardia. We should keep in mind that differentiation between intermittent and unapparent preexcitation is difficult, and some patients with unapparent preexcitation have short refractory periods of those accessory pathways, leading to sudden death. Abstract : This is a case of antidromic AVRT in a patient with unapparent pre‐excitation, and we could successfully diagnose and treat with the careful interpretation of wide QRS tachycardia. We should keep in mind that differentiation between intermittent and unapparent preexcitation is difficult, and some patients with unapparent pre‐excitation have short refractory periods of those accessory pathways, leading to sudden death.